2021
DOI: 10.48550/arxiv.2111.02433
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Three-Dimensional Real Space Invariants, Obstructed Atomic Insulators and A New Principle for Active Catalytic Sites

Abstract: Topologically trivial insulators come in two kinds: atomic, where the Wannier charge centers (WCCs) are localized on the atoms, and obstructed atomic, where the WCCs are located away from the atoms. The latter, which can exhibit interesting surface states and possibly have much larger band gaps than the topological insulators, have so far not been classified in three-dimensional (3D) crystalline materials. In this paper, we developed the 3D real space invariants (RSIs) for the 1,651 Shubnikov space groups with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(42 citation statements)
references
References 42 publications
3
39
0
Order By: Relevance
“…Although the band inversion typically signals to have nontrivial topological nature, both its topological indictor and mirror chern number equal to zero, indicating a topological trivial insulator. Furthermore, by deriving its electronic band structure of the edge boundary, metallic edge states nevertheless occur, which is very similar to the metallic surface states of 3D OAIs 45,46 . Interestingly, we further revealed that in total 16 monolayer MA 2 Z 4 semiconductors with 34 valence electrons (VEC) including experimentally synthesized ilar electronic band features to Îą 1 -WSn 2 N 4 and they all are topological trivial insulators.…”
mentioning
confidence: 79%
See 3 more Smart Citations
“…Although the band inversion typically signals to have nontrivial topological nature, both its topological indictor and mirror chern number equal to zero, indicating a topological trivial insulator. Furthermore, by deriving its electronic band structure of the edge boundary, metallic edge states nevertheless occur, which is very similar to the metallic surface states of 3D OAIs 45,46 . Interestingly, we further revealed that in total 16 monolayer MA 2 Z 4 semiconductors with 34 valence electrons (VEC) including experimentally synthesized ilar electronic band features to Îą 1 -WSn 2 N 4 and they all are topological trivial insulators.…”
mentioning
confidence: 79%
“…Recently, a series of unique topologically trivial insulators, dubbed obstructed atomic insulators (OAIs), have been found 45,46 . In difference from the BRs of atomic insulators induced from the atomic orbitals locating at atomoccupied Wyckoff positions (AOWPs), the BRs of OAIs are induced from additional atom-unoccupied Wyckoff positions (AUWPs).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The higher-order topology can be captured by topological quantum chemistry [13][14][15] , nested Wilson loop method 1,8 and second Stiefel-Whitney class [16][17][18][19][20][21][22] . Using topological quantum chemistry 13 , the HOTI can be diagnosed by the decomposition of atomic band representations (aBRs) as an unconventional insulator with mismatching of electronic charge centers and atomic positions 14,15,23 . In contrast to dipoles (Berry phase) for topological insulators, the HOTI can be understood by multipole moments 1 .…”
mentioning
confidence: 99%